Virtual water trade in dairy economy: irrigation water productivity in Gujarat - Singh, Om Prakash; Sharma, Amrita; Singh, Rahul; Shah, Tushaar (2004)
During the past 50 years, Gujarat has led India's exemplary growth in dairy production by forging the world's best known cooperative movement. Thanks to the market access and production enhancement programmes run by cooperatives, dairying has emerged at the centre stage of rural livelihoods systems in arid and semi-arid regions. However, intensification of dairying has been accompanied by intensive use of water used in growing feed and fodder. This study estimates that dairying-based rural livelihoods systems are now threatening the limited water resources of arid and semi-arid areas, and their future in turn is threatened by the depletion of these resources. The paper analyses virtual water exports and imports by some of the leading dairy cooperatives of Gujarat.